Primary small Bowel volvulus. - Paras, KP; Ashish, K; Ashwani, K; Pankaj, G; Nikhil, M; Arun, G (Department of Surgery, UKM Medical Centre, 2013)
Intestinal obstruction is a common surgical condition. It may be small bowel or large bowel obstruction. Small gut volvulus is rare in adults and usually presents with acute intestinal obstruction. We here report two cases with primary small bowel volvulus who presented with acute intestinal obstruction. The gangrenous gut was resected and end to end anastomosis done at laparotomy.